Cartilage‐Specific Autophagy Deficiency Promotes ER Stress and Impairs Chondrogenesis in PERK‐ATF4‐CHOP–Dependent Manner. (14th April 2017) - Kang, Xiaomin; Yang, Wei; Feng, Dongxu; Jin, Xinxin; Ma, Zhengmin; Qian, Zhuang; Xie, Tianping; Li, Huixia; Liu, Jiali; Wang, Ruiqi; Li, Fang; Li, Danhui; et al.
ABSTRACT: Autophagy is activated during nutritionally depleted or hypoxic conditions to facilitate cell survival. Because growth plate is an avascular and hypoxic tissue, autophagy may have a crucial role during chondrogenesis; however, the functional role and underlying mechanism of autophagy in regulation of growth plate remains elusive. In this study, we generated TamCart Atg7 –/– (Atg7cKO) mice to explore the role of autophagy during endochondral ossification. Atg7cKO mice exhibited growth retardation associated with reduced chondrocyte proliferation and differentiation, and increased chondrocyte apoptosis. Meanwhile, we observed that Atg7 ablation mainly induced the PERK‐ATF4‐CHOP axis of the endoplasmic reticulum (ER) stress response in growth plate chondrocytes. Although Atg7 ablation induced ER stress in growth plate chondrocytes, the addition of phenylbutyric acid (PBA), a chemical chaperone known to attenuate ER stress, partly neutralized such effects of Atg7 ablation on longitudinal bone growth, indicating the causative interaction between autophagy and ER stress in growth plate. Consistent with these findings in vivo, we also observed that Atg7 ablation in cultured chondrocytes resulted in defective autophagy, elevated ER stress, decreased chondrocytes proliferation, impaired expression of col10a1, MMP13, and VEGFA for chondrocyte differentiation, and increased chondrocyte apoptosis, while such effects were partly nullified by reduction of ER stress with PBA. In addition, Atg7 ablation‐mediated impaired chondrocyte function (chondrocyte proliferation, differentiation, and apoptosis) was partly reversed in CHOP –/– cells, indicating the causative role of the PERK‐ATF4‐CHOP axis of the ER stress response in the action of autophagy deficiency in chondrocytes. In conclusion, our findings indicate that autophagy deficiency may trigger ER stress in growth plate chondrocytes and contribute to growth retardation, thus implicating autophagy as an important regulator during chondrogenesis and providing new insights into the clinical potential of autophagy in cartilage homeostasis. © 2017 American Society for Bone and Mineral Research.